PENGARUH MUROTTAL AL-QURAN TERHADAP PENURUNAN NYERI PERSALINAN KALA I FASE AKTIF : EVIDENCE BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Pregnancy and childbirth are historic times in a woman's life cycle. In the process of childbirth a woman experiences a natural process that causes pain. Pain in labor is a normal condition, as long as it can be tolerated by the mother. The reduction of the pain scale during the labor process can be carried out through pharmacological and non-pharmacological measures. One of the non-pharmacological therapies that can be used to overcome labor pain is the distraction technique. Purpose: Murotal Al-Qur'an is one of the appropriate distraction techniques to reduce labor pain. The purpose of this report is to find out whether murottal Al-Quran can reduce labor pain in the first stage of active phase. Method: The article search method uses the Garuda and Google Schoolar databases. The intervention was carried out by playing Al-Quran verse from Surah Ar-Rahman using earphones and asking the mother to listen to it. Result: The report results from the assessment of maternal pain using the Numeric Rating Scale (NRS) before and after the intervention showed a significant difference with a decrease of 2 scales. Conclusion: Murottal Al-Quran is effective in reducing labor pain.